Antero-posterior Duplicate Exstrophy with a Wet Bladder Plate: A Diagnostic Dilemma - Thakkar, Nirali Chirag; Raj, Prince; Sarin, Yogesh Kumar (Journal of Neonatal Surgery, 2016)
Variants of exstrophy are rare anomalies seen in the spectrum of bladder exstrophy-epispadias complex. We present a rare case of duplicate exstrophy with a wet bladder plate. This is a deviation from the classical description of antero-posterior duplicate exstrophy that is associated with a dry bladder plate.